V.1 - "Johnson, Loch K.(ed.)" (London, 2007)
As the intelligence failures related to the 9/11 attacks and the misjudgments over weapons of mass destruction in Iraq attest, good intelligence is vital to America's security. Yet it has been neglected as a discipline for scholarly anaylsis. Recently, however, leading researchers have turned their attention to this subject. The opening volume in this set presents an array of approaches they have used to shed light on the place of intelligence in national security studies.
Keywords: Military intelligence